Effect of air bubble on inflammation after cataract surgery in rabbit eyes - Demirci, Göktuğ; Karabaş, Levent; Maral, Hale; Özdek, Şengül; Gülkılık, Gökhan (Wolters Kluwer Medknow Publications, 2013)
Purpose: Intense inflammation after cataract surgery can cause cystoid macular edema, posterior synechia and posterior capsule opacification. This experimental study was performed to investigate the effect of air bubble on inflammation when given to anterior chamber of rabbit eyes after cataract surgery. Materials and Methods: 30 eyes of 15 rabbits were enrolled in the study. One of the two eyes was in the study group and the other eye was in the control group. After surgery air bubble was given to the anterior chamber of the study group eye and balanced salt solution (BSS; Alcon) was left in the anterior chamber of control eye. Results: On the first, second, fourth and fifth days, anterior chamber inflammations of the eyes were examined by biomicroscopy. On the sixth day anterior chamber fluid samples were taken for evaluation of nitric oxide levels as an inflammation marker. When the two groups were compared, in the air bubble group there was statistically less inflammation was seen. (1, 2, 4. days P = 0,001, and 5. day P = 0,009). Conclusions: These results have shown that when air bubble is left in anterior chamber of rabbits’ eyes after cataract surgery, it reduced inflammation. We believe that, air bubble in the anterior chamber may be more beneficial in the cataract surgery of especially pediatric age group, uveitis patients and diabetics where we see higher inflammation. However, greater and long termed experimental and clinical studies are necessary for more accurate findings
Keywords: Air; Cataract Surgery; Inflammation; Rabbit